Differences in the type of vocabulary understood by deaf and hearing students: results to guide interventions. - González-Cuenca, Antonia Mercedes; González-Jerez, Marina; Linero-Zamorano, María José; Lavigne-Cerván, Rocío (Elsevier, 2024)
Vocabulary knowledge is an essential element in language development. There is evidence of significant differences in vocabulary knowledge between deaf children and hearing peers of the same age. These differences put deaf students at a disadvantage when compared to their hearing counterparts. The aim of this study was to investigate whether certain types of words characterise the lexical difficulties of deaf students. Our starting point is that this knowledge is needed to design interventions that are adapted to the particular needs of these students for their lexical development. We evaluated the lexical comprehension of 90 Spanish students. The sample comprised 45 hearing students and 45 students with severe or profound hearing loss. Both groups were attending the later years of primary school (8 to 12 years-old). They were tested using the Spanish Peabody Picture Vocabulary Test-III. The performance of both groups was statistically compared using percentiles and standard scores as well as a selected set of words from the test. No significant differences between hearing and deaf groups were found by age, sex, and sociocultural level. Significant differences were found between groups in their percentile and standard scores. There were no significant differences in performance between the two groups on only five of the 25 words with the highest error rate in the deaf group. The qualitative analysis of the remaining 20 words that were especially challenging for deaf students reveals results of interest which could help guide interventions. The results indicate the need for lexical intervention for deaf students in the final years of primary school. The specialised support service for deaf learners should approach the intervention by targeting a specific type of vocabulary, making the semantic relationships between these words more transparent and promoting a deeper understanding of them.
https://openpolicyfinder.jisc.ac.uk/id/publication/13827
Keywords: Niños con trastornos de audición; Orientación pedagógica; Deaf students; Vocabulary; Semantic relationships; Lexical intervention